The Regulation of Bacterial Biofilm Formation by cAMP-CRP: A Mini-Review - Liu, Cong; Sun, Di; Zhu, Jingrong; Liu, Jiawen; Liu, Weijie (Frontiers in Microbiology, 2020)
Biofilms are communities of microorganisms that live in a self-produced extracellular matrix in order to survive in hostile environments. Second messengers, such as c-di-GMP and cAMP, participate in the regulation of biofilm formation. c-di-GMP is a major molecule that is involved in modulating the bacterial transition between a planktonic lifestyle and biofilm formation. Aside from regulating carbon catabolism repression in most bacteria, cAMP has also been found to mediate biofilm formation in many bacteria. Although the underlying mechanisms of biofilm formation mediated by cAMP-CRP have been well-investigated in several bacteria, the regulatory pathways of cAMP-CRP are still poorly understood compared to those of c-di-GMP. Moreover, some bacteria appear to form biofilm in response to changes in carbon source type or concentration. However, the relationship between the carbon metabolisms and biofilm formation remains unclear. This mini-review provides an overview of the cAMP-CRP-regulated pathways involved in biofilm formation in some bacteria. This information will benefit future investigations of the underlying mechanisms that connect between biofilm formation with nutrient metabolism, as well as the cross-regulation between multiple second messengers.